THERMODYNAMIC ASSESSMENT OF WATER DIESEL EMULSIFIED FUEL USAGE IN A SINGLE CYLINDER DIESEL ENGINE. Issue 2 (1st June 2023) - Okumuş, Fatih; Kökkülünk, Görkem; Kaya, Cenk; Aydın, Zafer
ABSTRACT: In this study, 5% (W5), 10% (W10), and 15% (W15) of water-diesel emulsified fuels have been prepared using surfactants and obtained emulsifications were experimentally tested in a single-cylinder diesel engine on maximum torque and maximum power area at full load condition. In this way, theoretical analyses have been performed in order to evaluate the energy potential of a diesel engine fueled with emulsified fuel. According to results, thermal efficiency raises up to 9.4% with water amount increment since the reduction of work is smaller than the reduction of fuel energy rate. Fuel exergy rates increase up to 14.3% thanks to oxygen and hydrogen content of water but the destruction rate of exergy increased at the same time up to 25.2% and also exergetic efficiency reduces as up to 16.9% compared to neat diesel. Last of all, the ecological coefficient of performance (ECOP) criterion was obtained as 0.24 and 0.18 on maximum torque area and 0.28 and 0.21 on maximum power area for neat diesel and W15 as a disadvantage of water emulsified fuels.